Contemporary Black Theology: A Review Essay - Carter, J. Kameron (Modern theology, 2003)
Books reviewed in this article: Dwight N. Hopkins, Introducing Black Theology of Liberation Dwight N. Hopkins, Down, Up, and Over; Slave Religion and Black Theology Dwight N. Hopkins, Heart and Head: Black Theology-Past, Present, and Future